Engendering development: limits of feminist theories and justice - Verma, Vidhu (2004)
Recent feminist critiques of development have questioned some fundamental assumptions of feminist political theory; such critiques have also been successful in subverting long-held assumptions of conventional economic development. Viewed in the context of women's subordination in third world countries, a redefinition of development must not only be about economic growth, but ensure a redistribution of resources, challenge the gender-based division of labour and also seek to provide for an egalitarian basis in social arrangements. Further, as this article argues, any starting point for feminist critiques of development must also seek to link the end of gender oppression to multiple theories of justice - a justice not juridical but one that recognises the cultural membership of women in the community - Reproduced.
Keywords: Women